THE PRAGMATIC FUNCTIONS OF THE FRENCH LANGUAGE UNITS USED IN RUSSIAN LITERARY TEXTS - Khalmuradova Zebiniso Shavkatovna (International Journal of Literature and Language Studies, 2026)
The present article demonstrates analysis of pragmatic functions of the French language units used in Russian literary works. Such French borrowings fulfill stylistic, semantic and pragmatic functions and add special melody, beauty and sound to the text. The pragmatic features of linguistic activity, the factors that give rise to these features, is important for determining the social nature of the language. The extracts from original texts are compared with their Uzbek translation version.